The prevalence of occupational stress and its risk factors among private higher learning institutes (IPTS) lecturers in Malaysia - Tamilselvam, T. Nanthakumar (2021)
In Malaysia, the education sector is one of the industries with a huge number of employees. At this recent era, most private higher education institutions (IPTS) in Malaysia face a shortage of expertise, a high turnover rate of academicians, a higher demand for industrial reform and a weak incentive system. Therefore, it leads to potential psychological stress, musculoskeletal discomfort and job satisfaction that contributing occupational stress amongst its academician per ensuring the operational success. The study aimed to determine the relationship between occupational stress and its contributing factors among IPTS lecturers by utilizing cross sectional study design. A convenient sampling was used to obtain 380 IPTS lecturers throughout Malaysia. A set of questionnaires consist of sociodemographic profile, occupational stress index (OSI), psychological stress, musculoskeletal discomfort and job satisfaction questionnaire (JSQ) was used. The outcome reveals that 87.7% and 97.5% of academician experienced moderate to high occupational stress and psychological stress respectively, 96.3% with low to moderate level of musculoskeletal discomfort and 99.7% for moderate level of job satisfaction. There was a significant relationship between occupational stress and psychological stress and occupational stress with job satisfaction. In conclusion, it is believed that there are some underlying factors had managed to account medium to high level of occupational stress among the IPTS academician. However, it is unable to link if the underlying factors plays significant role in occupational stress in which it requires future in-depth analysis.